The impact of customer relationship management strategies on customer satisfaction under e-commerce platforms - Ding, Duo (2024)
This Dissertation examines the influence of various CRM strategies on customer satisfaction in the context of China's cross-border e-commerce platforms. The research employs a mixed-methods approach, including a questionnaire survey and advanced ordered logistic regression modeling. The study aims to identify key factors contributing to improved customer satisfaction by comparing the effectiveness of different CRM strategies from the user's perspective. The analysis considers various factors such as trust, loyalty, personalized recommendations, efficient customer service, and problem resolution. The findings provide insights for platform managers and policymakers on enhancing customer satisfaction, contributing to the discourse on cross-border e-commerce platforms and their role in global trade.